Politika zidu - Popović, Daniel (Teorija in praksa, 2012)
The text analyses in great detail the consequences of the restoration and fall of the Berlin Wall. The authors argue that specific policies concerning the wall could lead to the introduction of repressive measures, while a complete absence of policy on the wall might have unexpected consequences. They advocate the thesis that the clear orientation against the Berlin Wall has resulted in general disorientation - the bipolar world of capitalism and communism has been replaced by the one-dimensional world of neoliberal ideology. A purpose of the text is to show that the fall of the Iron Curtain also symbolises that part of the neoliberal revolution that has oppressed the world in the past three decades. The reunion of the Western and Eastern Blocs heralded unimaginable social changes. This is a period of the formation of the Slovenian state and the uncritical adoption of neoliberal policies.
Keywords: politics; politika; politika zidu; berlinski zid; Jugoslavija; Yugoslavia; slovenska država; Slovenia; Slovenija; šengenski režim; funkcije zidu; neoliberalizem